Effect of storage time on some quality parameters of calamondin (Citrus madurensis Lour.) squash stored at room temperature. - Nonmuang, W.; Pongsumran, S.; Mongkontanawat, N. (International Journal of Agricultural Technology, 2016)
Calamondin is a citrus fruit; known as one of the healthiest fruits suitable to make a drink, not only due to its high vitamin C content, but also its distinctive aroma and test. This study reported for some physical, chemical, and microbiological properties of 43oB and 60oB calamondin squash during 10-week storage at room temperature. The results showed that the L* values of 43oB and 60oB calamondin squash varied between 6.17-9.02 and 3.04-8.76, respectively. On week 6-10, b* values showed significantly lower compared to b* values on week 0. The sediment appeared on top of the bottle during storage. Storage time had no effect on total soluble solid and pH. Titratable acidity and ascorbic acid content declined with increase in storage duration on weeks 2-6. After 10 weeks, total microorganism including yeast and molds of calamondin squash were in the standard level.